Kekuatan Menentukan Dalam Perkembangan Islam di Sulawesi Selatan (Studi Abad XVI-XVII) - Aminuddin Raja (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
The histoy of Islamic spreading in South Sulawesi in 16-17 th century was determined by four factors, namely ; king, merchant, culture and ulama (preachers). From the four aspects, king was the dominant factor to influence the others. However, social communications resulted by moslem merchants also brought about the mutual understanding, so they (merchants) together with the religion (Islam) they were bringing were not considered strage by local community. The educated and enlightened merchants could muchly influence the social psychology that make people interested in adhering Islam as their religion.